Sustainable energy pricing - Zatzman, Gary. (Hoboken, N.J. : John Wiley & Sons ; Salem, Mass. : Scrivener Pub., 2012)
"The petroleum sector is possibly the largest and most dominant economic sector in the globalized economy. However, for reasons explored in this book, although none of the existing economic development models fit this sector in the past and apply even less today, no satisfactory alternative has presented itself. This book highlights the important reasons why current models fail to predict energy pricing with reasonable accuracy, and ventures into environmental and other problems with oil and gas production and associated economic decisions mounting across both developed as well as developing economies"--Provided by publisher.
"This book highlights the important reasons why current models fail to predict energy pricing with reasonable accuracy, and ventures into environmental and other problems with oil and gas production and associated economic decisions mounting across both developed as well as developing economies"--Provided by publisher.
.
Includes bibliographical references (p. 477-520) and index.
Keywords: Petroleum products -- Prices; Natural gas -- Prices; Petroleum industry and trade; Gas industry; Energy consumption; Energy development